2017
DOI: 10.1111/ans.14049
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatico‐jejunostomy decreases post‐operative pancreatic fistula incidence and severity after central pancreatectomy

Abstract: Backgrounds: Central pancreatectomy (CP) is an alternative to pancreaticoduodenectomy and distal pancreatectomy in benign tumours of pancreatic isthmus management. It is known for a high post-operative pancreatic fistula (POPF) rate. The purpose of this study was to compare POPF incidence between pancreatico-jejunostomy (PJ) and pancreaticogastrostomy (PG). Methods: Fifty-eight patients (mean age 53.9 AE 1.9 years) who underwent a CP in four French University Hospitals from 1988 to 2011 were analysed. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“… 68 A meta-analysis of eight RCTs comparing 607 patients who underwent PG and 604 patients who underwent PJ revealed a significant reduction in POPF with the PG technique. 69 However, a recent retrospective cohort study of 58 patients undergoing CP has demonstrated a higher rate of POPF in patients receiving PG as opposed to PJ. 70 The authors hypothesize that this may be due to a greater amount of tension that exists in a PG anastomosis as opposed to PJ.…”
Section: Traditional Conceptsmentioning
confidence: 99%
“… 68 A meta-analysis of eight RCTs comparing 607 patients who underwent PG and 604 patients who underwent PJ revealed a significant reduction in POPF with the PG technique. 69 However, a recent retrospective cohort study of 58 patients undergoing CP has demonstrated a higher rate of POPF in patients receiving PG as opposed to PJ. 70 The authors hypothesize that this may be due to a greater amount of tension that exists in a PG anastomosis as opposed to PJ.…”
Section: Traditional Conceptsmentioning
confidence: 99%
“…Lv et al [27] reported that overall complications rate of traditional CP was higher as compared with outcomes following DP (68.7 vs 23%, P = .003). It was also indicated that the overall complications rate of LCP and LSPDP groups in this study was lower than traditional CP and DP reported in literature, [20,27,28] that might attribute to the fact that laparoscopic surgery was more accurate and with less tissue injured. [10] POPF is considered as most spiny and risky complication after pancreatectomy.…”
Section: Discussionmentioning
confidence: 52%
“…In conventional CP procedure, the distal pancreas stump is anastomosed to the jejunum with Roux-en-Y enteroenterostomy reconstruction. [20] Compared with LSPDP, the additional reconstruction of LCP is more inconformity with physiological structure of human. It was shown that the postoperative exhaust time in patients undergoing LCP was significantly longer than LSPDP (4.4 ± 1.6 vs 2.5 ± 0.9 days, P = .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal, an article is accompanied by a Publisher's note to indicate that an earlier version of the paper was published elsewhere, reportedly without the author's consent and without the signature of a Copyright Agreement or License between the author and the Publisher. The matter was drawn to our attention by the authors and has been investigated by the Editorial Office.…”
mentioning
confidence: 99%